1981
DOI: 10.3758/bf03326971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of naloxone and housing conditions on shock-elicited reflexive fighting: Influence of immediate prior stress

Abstract: The effect of naloxone (4 mg!kg) on the defensive reaction of shock-elicited fighting was studied in male albino rats that were housed individually or in groups for 5 weeks. Naloxone consistently reduced the fighting reflex in both groups, but only when animals were exposed to the reflexive paradigm just prior to the naloxone injection and subsequently retested. Housing conditions also produced an effect on fighting independent of drug manipulation, in that individually housed animals exhibited decreased fight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Despite several methodological differences, the present study replicated results from the prior work of both Fanselow et al (1980) and McGivern et al (1981). Like Fanselow et aI., the present study demonstrates that naloxone can enhance defensive fighting in hooded rats.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Despite several methodological differences, the present study replicated results from the prior work of both Fanselow et al (1980) and McGivern et al (1981). Like Fanselow et aI., the present study demonstrates that naloxone can enhance defensive fighting in hooded rats.…”
supporting
confidence: 80%
“…The effect of the drug on the defensive fighting exhibited by rats shocked in pairs is less clear. McGivern, Lobaugh, and Collier (1981) reported that naloxone produces a reduction in the incidence of defensive fighting, whereas Fanselow, Sigmundi, and Bolles (1980) found that naloxone enhanced this response. Although many methodological differences exist between the two sets of studies, the present paper concentrates on one difference which may be critical in determin ing the direction of naloxone's effect on this fighting behavior.…”
mentioning
confidence: 99%